Memorial dedicated to Captain Frederick McGillivray - Ghosh, Ayan (2023)
Memorial dedicated to the memory of Captain Frederick McGillivray of the Bombay Engineers, who died on 25th March 1838, aged 37 years. At Bombay Castle, he served as an engineer at the Mint and was an early proponent for the establishment of a regular system of steam communication with Europe.